International Migration In Indonesia And Its Affecting Factors: Data Panel Approach - Fitra Prasapawidya Purna; Brylian Dwi Sulistian (Program Studi Ekonomi Syariah, 2019)
Availability of employment is a problem that arises in developing countries, which then causes the location to move or migrate from one place to another. The factors that influence the displacement are estimated in this study using the Random Effect model for panel data regression method in the provinces in Indonesia from 2010-2016. The results showed that three variables were found that had a significant effect: the human development index, the number of poor people, and the provincial minimum wage with positive influences for the two initial variables and the latter's negative effect towards migration. Simultaneously, the other two variables, namely the number of unemployed and gross regional domestic income per capita, did not significantly affect the negative influence on migration.